CAN WE PREDICT INCIPIENT DIABETES MELLITUS IN PATIENTS WITH TRANSFUSION DEPENDENT β-THALASSEMIA (β-TDT) REFERRED WITH A HISTORY OF PREDIABETES? - Vincenzo De Sanctis; Ashraf Soliman; Shahina Daar; Ploutarchos Tzoulis; Christos Kattamis (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Prediabetes and diabetes mellitus (DM) are complications in adult patients with transfusion dependent β-thalassemia (β-TDT), with their incidence increasing with age. Objective: This retrospective observational study describes the glycemic trajectories and evaluates predictive indices of β-cell function and insulin sensitivity/resistance in β-TDT patients with prediabetes, both in a steady state and during 3-h oral glucose tolerance test (OGTT), in order to identify patients at high risk for incipient diabetes. Setting: The study was mainly conducted at the Pediatric and Adolescent Outpatient Clinic, Quisisana Hospital, Ferrara (Italy) in collaboration with thalassemia referring centers across Italy. Patients: The study included 11 β-TDT (aged 15.11- 31.10 years) with history of prediabetes. Methods: The ADA criteria for the diagnosis of glucose dysregulation were adopted. Investigations included evaluation of plasma glucose levels and insulin secretion, analysis of glycemic trajectories and indices of β-cell function and insulin sensitivity/resistance assessed in steady state and during OGTT. Results: The duration of progression from prediabetes to DM, expressed in years, showed a positive direct correlation with corrected insulin response (CIR-30 = r: 0.7606, P: 0.0065), insulinogenic index (IGI 0-120 = r: 0.6121, P:0.045), oral disposition index (oDI = r: 0.7119, P:0.013), insulin growth factor-1 (IGF-1= r: 0.6246, P: 0.039) and an inverse linear correlation with serum ferritin (SF = r: -0.7197, P: 0.012). Conclusions: Progressive β-cell failure, peripheral resistance to the action of insulin and reduction of oDI were the principal factors responsible for the progression from prediabetes to incipient DM.